Impact of Transition Metal Layer Vacancy on the Structure and Performance of P2 Type Layered Sodium Cathode Material - Zhanadilov, Orynbay; Baiju, Sourav; Voronina, Natalia; Yu, Jun Ho; Kim, A.‑Yeon; Jung, Hun‑Gi; Ihm, Kyuwook; Guillon, Olivier; Kaghazchi, Payam; Myung, Seung‑Taek (Nano-Micro Letters, 2024)
This study explores the impact of introducing vacancy in the transition metal layer of rationally designed Na0.6[Ni0.3Ru0.3Mn0.4]O2 (NRM) cathode material. The incorporation of Ru, Ni, and vacancy enhances the structural stability during extensive cycling, increases the operation voltage, and induces a capacity increase while also activating oxygen redox, respectively, in Na0.7[Ni0.2VNi0.1Ru0.3Mn0.4]O2 (V-NRM) compound. Various analytical techniques including transmission electron microscopy, X-ray absorption near edge spectroscopy, operando X-ray diffraction, and operando differential electrochemical mass spectrometry are employed to assess changes in the average oxidation states and structural distortions. The results demonstrate that V-NRM exhibits higher capacity than NRM and maintains a moderate capacity retention of 81% after 100 cycles. Furthermore, the formation of additional lone-pair electrons in the O 2p orbital enables V-NRM to utilize more capacity from the oxygen redox validated by density functional calculation, leading to a widened dominance of the OP4 phase without releasing O2 gas. These findings offer valuable insights for the design of advanced high-capacity cathode materials with improved performance and sustainability in sodium-ion batteries. Highlights: 1 Vacancy in the transition metal layer of sodium cathode material induces the formation lone-pair electrons in the O 2p orbital. 2 Material delivers more capacity from the oxygen redox validated by density functional calculation. 3 Widened dominance of the OP4 phase without releasing O2 gas.